Restoring small water bodies to improve lake and river water quality in China - Wangzheng Shen; Liang Zhang; Emily A. Ury; Sisi Li; Biqing Xia; Nandita B. Basu (Nature Communications)
Abstract Climate change, population growth, and agricultural intensification are increasing nitrogen (N) inputs, while driving the loss of inland water bodies that filter excess N. However, the interplay between N inputs and water body dynamics, and its implications for water quality remain poorly understood. Analyzing data from 1995 to 2015 across China, here, we find a 71% reduction in the area of small (<104.5 m2) water bodies (SWB), primarily in high-N-input agricultural regions. Preferential loss of SWBs, the most efficient nutrient filters, places 42% of China at high water quality risk due to increasing N inputs and declining SWB density. Currently, N removal by water bodies is 986 kilotonnes year−1, but restoring 2.3 million hectares of SWB could increase removal by 21%, compared to just 5% for equivalent restoration of large water bodies. Targeted SWB restoration is crucial for improving water quality and mitigating N pollution in China.